First aid, CPR, and AED. - Thygerson, Alton L.; Thygerson, Steven M.; Gulli, Benjamin; Piazza, Gina M. (Jones & Bartlett Learning, 2012)
This concise student manual is designed to give laypersons the education and confidence they need to effectively provide emergency care.